2020
DOI: 10.1002/advs.201903366
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Receptor 1 Regulates Thermogenic Capacity and Cell Fate in Brown/Beige Adipocytes

Abstract: Iron homeostasis is essential for maintaining cellular function in a wide range of cell types. However, whether iron affects the thermogenic properties of adipocytes is currently unknown. Using integrative analyses of multi‐omics data, transferrin receptor 1 (Tfr1) is identified as a candidate for regulating thermogenesis in beige adipocytes. Furthermore, it is shown that mice lacking Tfr1 specifically in adipocytes have impaired thermogenesis, increased insulin resistance, and low‐grade inflammation accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…Under physiological conditions, ferric iron in the form of transferrin-bound iron (TBI) recognized by membrane Tfr1 is absorbed in peripheral tissues, such as liver, adipose tissue, skeletal muscle, and bone marrow (23, 41, 42) . Multiple studies have shown that Tfr1 -deficiency results in functional disorder and even death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, ferric iron in the form of transferrin-bound iron (TBI) recognized by membrane Tfr1 is absorbed in peripheral tissues, such as liver, adipose tissue, skeletal muscle, and bone marrow (23, 41, 42) . Multiple studies have shown that Tfr1 -deficiency results in functional disorder and even death.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with Tfr1 conditional knockout in hematopoietic stem cells died within one week after birth (43) . Our previous study demonstrated that Tfr1 regulates adipocyte thermogenesis and cell fate determination (44) . Adipocytes with Tfr1 ablation exhibit reduced thermogenic capacity and beigeing potential (44) .…”
Section: Discussionmentioning
confidence: 99%
“…To study the effects of adipocyte-specific iron homeostasis on metabolism, models in which iron import and export proteins have been ablated, provide important insights. Adipocyte-targeted knock down of iron handling proteins [ 31 , 40 ] in vitro and in vivo are generally associated with dysfunctional elevation in inflammation and reductions in insulin signaling. For example, human adipocytes lacking lactoferrin showed increased expression of inflammatory genes [ 31 ].…”
mentioning
confidence: 99%
“…On a high-fat diet, these mice have increased markers of AT inflammation, dysregulated lipid metabolism, mount a defective thermogenic response, and develop insulin resistance. Interestingly, these effects were thought to be regulated by HIF1α activation in beige adipocytes [ 40 ]. This is entirely in line with the observations noted above in the KK/HIJ and obese anemic mice [ 32 , 37 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation